Resource allocation in metabolic networks: kinetic optimization and approximations by FBA. (27th November 2015) - Müller, Stefan; Regensburger, Georg; Steuer, Ralf
Abstract : Based on recent theoretical results on optimal flux distributions in kinetic metabolic networks, we explore the congruences and differences between solutions of kinetic optimization problems and results obtained by constraint-based methods. We demonstrate that, for a certain resource allocation problem, kinetic optimization and standard flux balance analysis (FBA) give rise to qualitatively different results. Furthermore, we introduce a variant of FBA, called satFBA, whose predictions are in qualitative agreement with kinetic optimization.